AGRESIVITAS VERBAL MAHASISWA PENGGUNA MEDIA SOSIAL: BAGAIMANA PERAN REGULASI EMOSI? - Nia Lestari, Sofiyah; Sri Lestari, Bawinda; Puspitasari, Devi (Pusat Studi GESI - UWP, 2023)
This study aims to determine the relationship between emotion regulation and verbal aggressiveness in students who use social media. The population of this study were students who used social media in one of the campuses in Surabaya. The research sample amounted to 127 people selected using simple random sampling technique. Data collection used two psychological scales, namely the Verbal Aggressiveness Scale (VAS) from Infante and Wigley and the Emotion Regulation Questionnaire (ERQ) scale adapted from Gross and John. The data analysis technique in this study used product moment correlation. The results of this study indicate that there is a negative relationship between emotion regulation and verbal aggressiveness in students who use social media.